Towards two-photon interference with a whispering gallery photon pair source - Schunk, Gerhard; Shafiee, Golnoush; Vogl, Ulrich; Strekalov, Dmitry; Otterpohl, Alexander; Sedlmeir, Florian; Schwefel, Harald G.L.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2016)
Down-converted photons from counterpropagating whispering gallery modes can be used to generate two-photon interference. We present our experimental scheme and discuss the interference visibility in case of backscattering.
CRIS-Team Scopus Importer:2022-06-05